NUMERICAL APPROACH IN AEROELASTICITY - Oskar SLOBODA; Peter KORBA; Michal HOVANEC; Jan PILA (Scientific Journal of Silesian University of Technology. Series Transport)
Aircraft wing design processes should comprise specific analyses oriented towards aeroelasticity, which is one of the essential factors determining flight envelope boundaries. For such cases, static or dynamic aeroelastic phenomena can be simulated using CFD simulation software. ANSYS software offers the fluid structure interaction (FSI) method for solving this multiphysics problem